When Strong Institutions Meet Weak Economies: Lessons from Ecotourism Sustainability in Lombuyan Wildlife Sanctuary, Central Sulawesi - Lalu, Andika; Ramlah, Sitti; Reinaldi, Reinaldi; lalu, andika lalu (Forestry Department, University of Muhammadiyah Makassar, 2025)
Ecotourism in conservation areas has significant potential to enhance local livelihoods while supporting ecosystem protection. Sustainability, however, strongly depends on institutional capacity. This study assesses the sustainability status of ecotourism in the Lombuyan Wildlife Sanctuary (KSM Lombuyan), Banggai Regency, Central Sulawesi, by integrating ecological, economic, social, and institutional dimensions using the Rap_Ecotourism method, a multidisciplinary rapid appraisal adapted from the Multidimensional Scaling (MDS) approach. Data were collected from October to December 2024 through interviews, ground checks, observations and documentation. The analysis results indicate that the overall sustainability index of the Lombuyan ecotourism area is 63.89%, classified as moderately sustainable. Among the four dimensions: the institutional dimension achieved the highest index (82.37%), followed by the social dimension (80.09%), while the ecological (55.18%) and economic (33.13%) dimensions were relatively lower. The results highlight that the traditional institution Pololuanto Lombuyan plays a crucial role in maintaining governance, enforcing local rules and facilitating collaboration between the community and the Central Sulawesi Natural Resources Conservation Agency (BKSDA). This strong institutional framework compensates for economic limitations and supports ecological rehabilitation, particularly through community-led land restoration and monitoring. Our findings reveal that the sustainability of the Lombuyan ecotourism area is strongly influenced by resilience of local institutions and community participation. Strengthening these governance mechanisms offers a viable pathway for improving the long-term sustainability of ecotourism in conservation landscapes.